Multi-wavelength photometry during the 2018 superoutburst of the WZ Sge-type dwarf nova EG Cancri. (2nd October 2020) - Kimura, Mariko; Isogai, Keisuke; Kato, Taichi; Kojiguchi, Naoto; Wakamatsu, Yasuyuki; Ohnishi, Ryuhei; Sugiura, Yuki; Matsumoto, Hanami; Sumiya, Sho; Ito, Daiki; Nikai, Kengo; Matsumoto, Katsura; et al.
Abstract: We report on the multi-wavelength photometry of the 2018 superoutburst in EG Cnc. We have detected stage A superhumps and long-lasting late-stage superhumps via the optical photometry and have constrained the binary mass ratio and its possible range. The median value of the mass ratio is 0.048 and the upper limit is 0.057, which still implies that EG Cnc is one of the possible candidates for period bouncers. This object also showed multiple rebrightenings in this superoutburst which are the same as those in its previous superoutburst in 1996–1997, despite the difference in the main superoutburst. This would represent that the rebrightening type is inherent to each object and is independent of the initial disk mass at the beginning of superoutbursts. We also found that B − I and J − K s colors were unusually red just before the rebrightening phase and became bluer during the quiescence between rebrightenings, which would mean that the low-temperature mass reservoir at the outermost disk accreted with time after the main superoutburst. Also, the ultraviolet flux was sensitive to rebrightenings as well as the optical flux, and the U − B color became redder during the rebrightening phase, which would indicate that the inner disk became cooler when this object repeated rebrightenings. Our results thus basically support the idea that the cool mass reservoir in the outermost disk is responsible for rebrightenings.